2016
DOI: 10.5811/westjem.2015.11.28715
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Status with Severity and Management in ED Patients with Asthma Exacerbation

Abstract: IntroductionPrevious studies have demonstrated an association of low socioeconomic status with frequent asthma exacerbations. However, there have been no recent multicenter efforts to examine the relationship of insurance status – a proxy for socioeconomic status – with asthma severity and management in adults. The objective is to investigate chronic and acute asthma management disparities by insurance status among adults requiring emergency department (ED) treatment in the United States.MethodsWe conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
4
10
1
Order By: Relevance
“…6,32 Similar to prior studies, we attempted to control for social factors using insurance status and demographic characteristics as surrogate markers. 33,34 While this is a limited marker of socioeconomic status, we did not observe a significant relationship between insurance type and risk of readmission.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…6,32 Similar to prior studies, we attempted to control for social factors using insurance status and demographic characteristics as surrogate markers. 33,34 While this is a limited marker of socioeconomic status, we did not observe a significant relationship between insurance type and risk of readmission.…”
Section: Resultscontrasting
confidence: 80%
“…Other social factors that have been shown to affect readmission, for which we were not able to fully account, such as employment status, education level and socioeconomic status, may have influenced readmission rates in our patient population . Similar to prior studies, we attempted to control for social factors using insurance status and demographic characteristics as surrogate markers . While this is a limited marker of socioeconomic status, we did not observe a significant relationship between insurance type and risk of readmission.…”
Section: Discussionmentioning
confidence: 90%
“…Access to a doctor for asthma care because of high out-of-pocket costs was disproportionately lower for children who were uninsured, had public health insurance, or partial year coverage compared with insured, private insurance, and full year insurance coverage, respectively. This finding is not unexpected and supported by literature because uninsured children are less likely to have specialist care and medication use compared with insured children [19]. Hasegawa et al [19] found that patients with no insurance used fewer asthma control medications and were less likely to have asthma specialist care.…”
Section: Discussionsupporting
confidence: 63%
“…Some research has evaluated whether public insurance coverage, commonly associated with minority status, is associated with lower rates of controller medication prescription and use than private insurance coverage. In 2 studies that assessed prescription patterns, 1 through chart review of emergency department records adults with asthma 57 and the other by evaluation of electronic medical record among children with asthma, 58 there were no differences in prescription rates of controller medication by insurance status (public vs private). In contrast, there are data to suggest differential patterns of controller medication prescription upon hospital discharge by insurance status.…”
Section: Insurance Coveragementioning
confidence: 99%
“…27,32 Health care provider biases and communication patterns with culturally diverse patients, particularly those with LEP, likely affect providers' skill in communicating about controller medication use in a culturally sensitive manner. 49,50 Systems factors, such as health care coverage, 57,58 cost, 61 and features of the community environment such as exposure to violence, 59 also present challenges to effective disease management and consistent medication use. What then, can be done to address these disparities in medication use and subsequent outcomes?…”
Section: Conclusion and Potential Intervention Strategiesmentioning
confidence: 99%